A new resin glycoside from Calystegia soldanella and its antiviral activity towards herpes. Issue 22 (17th November 2017) - Ono, Masateru; Kanemaru, Yukiyo; Yasuda, Shin; Okawa, Masafumi; Kinjo, Junei; Miyashita, Hiroyuki; Yokomizo, Kazumi; Yoshimitsu, Hitoshi; Nohara, Toshihiro
Abstract: A new resin glycoside, named calysolin XVIII (1 ), was isolated from the leaves, stems and roots of Calystegia soldanella Roem. et Schult. (Convolvulaceae). The structure of1 was defined as 11 S -jalapinolic acid 11- O -β-d -glucopyranosyl-(1 → 3)- O -(2- O -2 S -methylbutyryl, 4- O -3-hydroxy-2-methylenebutyryl)-α-l -rhamnopyranosyl-(1 → 2)-[ O -β-d -glucopyranosyl-(1 → 6)- O -(34-di- O -2 S -methylbutyryl)-β-d -glucopyranosyl-(1 → 3)]- O -β-d -glucopyranosyl-(1 → 2)-β-d -quinovopyranoside, intramolecular 1, 2″′″′-ester on the basis of spectroscopic data. Compound1 is the first known resin glycoside to feature 3-hydroxy-2-methylenebutyric acid as a component organic acid. In addition, 1 demonstrated an antiviral activity against herpes simplex virus type 1, with an IC50 value 2.3 μM. Abstract :